Cognitive Challenge in Translation and Interpreting Studies - Putu Desi Anggerina Hikmaharyanti; Ni Made Verayanti Utami; I Gusti Agung Sri Rwa Jayantini; Ni Nyoman Deni Ariyaningsih (RETORIKA: Jurnal Ilmu Bahasa, 2023)
The field of Translation and Interpreting (T&I) encompasses bilingual activities in transferring messages from a source language to a target language with an assertive cognitive capacity to produce natural and equivalent meaning. This study serves as a preliminary experiment to explore the cognitive capacity development of ESL students in rendering messages within T&I. Mix-method is applied by involving 28 students taking the test of rendering the messages orally and in written. The experiment consists of three stages: a CEFR test, which reveals that the students' highest level is B1 Intermediate; a 12-session T&I course covering theory, strategies, and practice; and an evaluation phase including feedback collected through questionnaires. In general, the T&I process of rendering messages from English (EN) to Indonesian (ID) is deemed naturally acceptable, and the students are able to accomplish the task. However, there are challenges related to working memory, which result in students not achieving excellent test scores. The EN-ID group shows better performance in translating and interpreting, particularly in the higher score ranges, whereas the ID-EN group has a larger number of participants with lower scores. Additionally, delivering messages from Indonesian to English poses challenges, especially in the context of noun phrases. These challenges are primarily attributed to differences in word order, determiners and articles, prepositions, idiomatic expressions, vocabulary, as well as the participants' proficiency level and exposure to both languages.